Efficient top layer configuration in parquet production. Issue 4 (3rd April 2021) - Kaltenbrunner, Matthias; Huka, Maria Anna; Gronalt, Manfred
ABSTRACT: This article concerns the optimized planning of the assembly of the top layer of floorboards in the parquet industry. This layer is constructed with lamellas of different lengths and grades that are aligned into three lanes. The grades used and the arrangement of the lamellas define the quality of the floorboard produced. This results in a large number of pattern permutations that must be considered during production planning. Hence, a mixed integer program is developed here in order to minimize the total production cost. First, it is shown how to reduce the number of patterns without constraining the feasible region. Secondly, numerical studies with different pattern selection strategies are carried out. This reveals that only a very small fraction of the total number of patterns is necessary in order to achieve results which are close to the global optimum and fast enough for an industrial application.